Can the Vocal Expression of Intellectually Disabled Individuals Be Used as a Pain Indicator? Initial Findings Supporting a Possible Novice Assessment Method - Icht, Michal; Wiznitser Ressis-tal, Hadar; Lotan, Meir (Frontiers in Psychology, 2021)
Pain is difficult to assess in non-verbal populations such as individuals with intellectual and developmental disability (IDD). Due to scarce research in this area, pain assessment for individuals with IDD is lacking, leading to maltreatment. To improve medical care for individuals with IDD, immediate, reliable, easy to use pain detection methods should be developed. The goal of this preliminary study was to examine the sensitivity of acoustic features of vocal expressions in identifying pain for adults with IDD, assessing their feasibility as a pain detection indicator. Such unique pain related vocal characteristics may be used to develop objective pain detection means. Fifteen adults with severe-profound IDD level were recorded in daily activities associated with pain (during diaper changes), or without pain (at rest). Spontaneous vocal expressions were acoustically analyzed to assess several voice characteristics. Analyzing the data revealed that pain related vocal expressions were characterized by significantly higher number of pulses and higher shimmer values relative to no-pain vocal expressions. Pain related productions were also characterized by longer duration, higher jitter, lower Harmonic-Noise Ratio, lower difference between the amplitude of the 1st and 2nd harmonic (corrected for vocal tract influence; H1H2c), and higher mean and standard deviation of voice fundamental frequency relative to no-pain vocal productions, yet these findings were not statistically significant, possibly due to the small and heterogeneous sample. These initial results may prompt further research to explore the possibility to use pain related vocal output as an objective and easily identifiable indicator of pain in this population.